Assessing The Redistributive Effect of Fiscal Policy - Essama-Nssah, Boniface, 1949- 1949- (The World Bank, 2008)
Who benefits from public spending? Who bears the burden of taxation? How desirable is the distribution of net benefits from the operation of a tax-benefit system? This paper surveys basic concepts, methods, and modeling approaches commonly used to address these issues in the context of fiscal incidence analysis. The review covers the incidence of both taxation and public spending. Methodological points are supported by country cases. The effective distribution of benefits and burdens associated with fiscal policy depends on the size of the government, the distributive mechanisms involved, and the incentives properties of the policy under consideration. This creates a need for analytical methods to account for both individual behavior and social interaction. The approaches reviewed include simple reduced form regression analysis, microsimulation models (both the envelope and discrete choice models), computable general equilibrium modeling, and approaches that link computable general equilibrium models to microsimulation models. Explicit modeling facilitates the construction of counterfactuals to back up causal analysis. Social desirability is assessed on the basis of progressivity along with deadweight loss